PENGARUH KARATERISTIK INDIVIDUAL TERHADAP STRES KERJA PERAWAT DI RUANG RAWAT INAP RUMAH SAKIT UMUM ROYAL PRIMA TAHUN 2021 - Raja Imam Hidayat Siregar (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2021)
The quality of service that requires nurses to be maximal in providing health services. Complaints and negative responses from patients become a burden for nurses. The workload with different characteristics of each nurse causes work stress. The general objective of the study was to understand the impact of individual characteristics with regard to feelings of worry, anxiety in the hospital room of the Royal Prima General Hospital. The specific objectives of the study are based on the characteristics of age, sex and years of service. The type of observation used descriptive analytic observation with cross sectional method. The population in this observation is all nurses in the hospital as many as 350 people. Nurses in the hospitalization section were taken as respondents in the observation of 30 respondents. The sample in this study were 30 respondents. Chi-Square test results based on age with a value of sig = 10.253 and a value of df = 9.488, with α = 0.05, then 10.253> 9.488, so there is an effect of age characteristics on the work stress of nurses. Based on gender with sig = 2.037 and df = 5.991, then 2.037 <5.991, so there is no effect of gender characteristics on the work stress of nurses. Based on the tenure with the sig = 9.620 and the df = 9.488, then 9.620> 9.488, so there is an effect of tenure characteristics on nurses' work stress. The conclusion of this study is that there is an influence on the characteristics of age, years of service and there is no effect of gender with regard to feelings of worry, uneasiness of nurses in the hospital room of the Royal Prima General Hospital in 2021.